The global fatty liver disease Sustainable Development Goal country score for 195 countries and territories (2023)
ABSTRACT: Background and Aims: Fatty liver disease is highly prevalent, resulting in overarching wellbeing and economic costs. Addressing it requires comprehensive and coordinated multisectoral action. We developed a fatty liver disease Sustainable Development Goal (SDG) country score to provide insights into country-level preparedness to address fatty liver disease through a whole-of-society lens. Approach and Results: We developed 2 fatty liver disease–SDG score sets. The first included 6 indicators (child wasting, child overweight, noncommunicable disease mortality, a universal health coverage service coverage index, health worker density, and education attainment), covering 195 countries and territories between 1990 and 2017. The second included the aforementioned indicators plus an urban green space indicator, covering 60 countries and territories for which 2017 data were available. To develop the fatty liver disease–SDG score, indicators were categorized as “positive” or “negative” and scaled from 0 to 100. Higher scores indicate better preparedness levels. Fatty liver disease–SDG scores varied between countries and territories (n = 195), from 14.6 (95% uncertainty interval: 8.9 to 19.4) in Niger to 93.5 (91.6 to 95.3) in Japan; 18 countries and territories scored > 85. Regionally, the high-income super-region had the highest score at 88.8 (87.3 to 90.1) in 2017, whereas south Asia had the lowest score at 44.1 (42.4 to 45.8). Between 1990 and 2017, the fatty liver disease–SDG score increased in all super-regions, with the greatest increase in south Asia, but decreased in 8 countries and territories. Conclusions: The fatty liver disease–SDG score provides a strategic advocacy tool at the national and global levels for the liver health field and noncommunicable disease advocates, highlighting the multisectoral collaborations needed to address fatty liver disease, and noncommunicable diseases overall.